Dementia Friendly, Dementia Capable, and Dementia Positive: Concepts to Prepare for the Future. (15th February 2015) - Lin, Shih-Yin; Lewis, Frances Marcus
Abstract : With an aging global population, the number of dementia cases is growing exponentially. To address the upcoming dementia crisis, the World Health Organization and Alzheimer's Disease International (2012) collaborated on an extensive report, Dementia: A Public Health Priority . In the United Kingdom, Prime Minster David Cameron initiated a national challenge on dementia, forming 3 dementia challenge champion groups aimed at improving health and care, creating dementia-friendly communities, and promoting dementia research. In the U.S., President Obama signed the National Alzheimer's Project Act, which led to the formation of the Advisory Council on Alzheimer's Research, Care, and Services and the launch of the first National Plan to Address Alzheimer's Disease. The term "dementia capable" was introduced in the 2012 Recommendations of the Public Members of the Advisory Council and has since been adopted in both the recommendations and annual updates of the national plan. This paper will first compare and contrast government usage of the concepts dementia friendly and dementia capable, along with another valuable concept, dementia positive, that was added after reviewing the literature. Finally, a new vision statement for the U.S.' national plan will be proposed and recommendations incorporating these 3 concepts in policy, research, and practice will be made.